Sensitivity analysis of dissipation parameterizations in a third-generation spectral wave model, WAVEWATCH III for Indian Ocean. (15th September 2016) - Seemanth, M.; Bhowmick, Suchandra Aich; Kumar, Raj; Sharma, Rashmi
Abstract: Present study determines sensitivity of different input and dissipation parameterization schemes available in a third-generation wind-wave model, WAVEWATCH III for Indian Ocean (IO), using collocated altimeter and in-situ buoy measurements. For IO, in general, parameterization by Bidlot et al. (2005, referred as BAJ) is found to be the best in simulating SWH, for all the seasons. Albeit NIO is a part of IO, wave climate over this region is different as it exhibits variability in surface wind conditions before, after and during the monsoon phase. Thus, over NIO during pre- and post- monsoon seasons, when the region is dominated by swells propagating from the south, KC (KC denotes Kahma and Calkoen (1992, 1994)) stable parameterization scheme of Tolman and Chalikov (1996) is the better option for input and dissipation source function. During monsoon season, waves over NIO is primarily influenced by strong and persistent southwest monsoonal winds and dominated by young wind seas. BAJ parameterization is suggested as the better option during this phase. To simulate the high waves induced by tropical cyclones, KC stable parameterization of Tolman and Chalikov (1996) is found suitable. Highlights: Analysed the sensitivity of dissipation parameterizations in WW3 for Indian Ocean. For Indian Ocean, BAJ scheme is the best in simulating SWH during all the seasons. For NIO during non-monsoon seasons, Tolman and Chalikov scheme is the better option. During monsoon season BAJ parameterization is identified as the better option. To simulate the high wave conditions, Tolman and Chalikov scheme is suitable.